Antiplatelet Therapy in Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (STROKE, 2019)
CRIS-Team WoS Importer:2019-08-23

Antiplatelet Therapy in Primary Spontaneous and Oral Anticoagulation-Associated Intracerebral Hemorrhage - Sprügel, Maximilian; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Beuscher, Vanessa D.; Hagen, Manuel; Röder, Sebastian; Lücking, Hannes; Struffert, Tobias; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen (Stroke, 2018)
Background and Purpose- This study determined the influence of concomitant antiplatelet therapy (APT) on hematoma characteristics and outcome in primary spontaneous intracerebral hemorrhage (ICH), vitamin K antagonist (VKA)- and non-VKA oral anticoagulant-associated ICH. Methods- Data of retrospective cohort studies and a prospective single-center study were pooled. Functional outcome, mortality, and radiological characteristics were defined as primary and secondary outcomes. Propensity score matching and logistic regression analyses were performed to determine the association between single or dual APT and hematoma volume. Results- A total of 3580 patients with ICH were screened, of whom 3545 with information on APT were analyzed. Three hundred forty-six (32.4%) patients in primary spontaneous ICH, 260 (11.4%) in VKA-ICH, and 30 (16.0%) in non-VKA oral anticoagulant-associated ICH were on APT, and these patients had more severe comorbidities. After propensity score matching VKA-ICH patients on APT presented with less favorable functional outcome (modified Rankin Scale score, 0-3; APT, 48/202 [23.8%] versus no APT, 187/587 [31.9%]; P=0.030) and higher mortality (APT, 103/202 [51.0%] versus no APT, 237/587 [40.4%]; P=0.009), whereas no significant differences were present in primary spontaneous ICH and non-VKA oral anticoagulant-associated ICH. In VKA-ICH, hematoma volume was significantly larger in patients with APT (21.9 [7.4-61.4] versus 15.7 [5.7-44.5] mL; P=0.005). Multivariable regression analysis revealed an association of APT and larger ICH volumes (odds ratio, 1.80 [1.20-2.70]; P=0.005), which was more pronounced in dual APT and supratherapeutically anticoagulated patients. Conclusions- APT does not affect ICH characteristics and outcome in primary spontaneous ICH patients; however, it is associated with larger ICH volume and worse functional outcome in VKA-ICH, presumably by additive antihemostatic effects. Combination of anticoagulation and APT should, therefore, be diligently evaluated and restricted to the shortest possible time frame.
EVALuna2:34909

Association of Surgical Hematoma Evacuation vs Conservative Treatment With Functional Outcome in Patients With Cerebellar Intracerebral Hemorrhage - Kuramatsu, Joji; Biffi, Alessandro; Gerner, Stefan; Sembill, Jochen; Sprügel, Maximilian; Leasure, Audrey; Sansing, Lauren; Matouk, Charles; Falcone, Guido J.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; et al. (Journal of the American Medical Association, 2019)
Importance: The association of surgical hematoma evacuation with clinical outcomes in patients with cerebellar intracerebral hemorrhage (ICH) has not been established. Objective: To determine the association of surgical hematoma evacuation with clinical outcomes in cerebellar ICH. Design, Setting, and Participants: Individual participant data (IPD) meta-analysis of 4 observational ICH studies incorporating 6580 patients treated at 64 hospitals across the United States and Germany (2006-2015). Exposure: Surgical hematoma evacuation vs conservative treatment. Main Outcomes and Measures: The primary outcome was functional disability evaluated by the modified Rankin Scale ([mRS] score range: 0, no functional deficit to 6, death) at 3 months; favorable (mRS, 0-3) vs unfavorable (mRS, 4-6). Secondary outcomes included survival at 3 months and at 12 months. Analyses included propensity score matching and covariate adjustment, and predicted probabilities were used to identify treatment-related cutoff values for cerebellar ICH. Results: Among 578 patients with cerebellar ICH, propensity score-matched groups included 152 patients with surgical hematoma evacuation vs 152 patients with conservative treatment (age, 68.9 vs 69.2 years; men, 55.9% vs 51.3%; prior anticoagulation, 60.5% vs 63.8%; and median ICH volume, 20.5 cm3 vs 18.8 cm3). After adjustment, surgical hematoma evacuation vs conservative treatment was not significantly associated with likelihood of better functional disability at 3 months (30.9% vs 35.5%; adjusted odds ratio [AOR], 0.94 [95% CI, 0.81 to 1.09], P = .43; adjusted risk difference [ARD], -3.7% [95% CI, -8.7% to 1.2%]) but was significantly associated with greater probability of survival at 3 months (78.3% vs 61.2%; AOR, 1.25 [95% CI, 1.07 to 1.45], P = .005; ARD, 18.5% [95% CI, 13.8% to 23.2%]) and at 12 months (71.7% vs 57.2%; AOR, 1.21 [95% CI, 1.03 to 1.42], P = .02; ARD, 17.0% [95% CI, 11.5% to 22.6%]). A volume range of 12 to 15 cm3 was identified; below this level, surgical hematoma evacuation was associated with lower likelihood of favorable functional outcome (volume ≤12 cm3, 30.6% vs 62.3% [P = .003]; ARD, -34.7% [-38.8% to -30.6%]; P value for interaction, .01), and above, it was associated with greater likelihood of survival (volume ≥15 cm3, 74.5% vs 45.1% [P < .001]; ARD, 28.2% [95% CI, 24.6% to 31.8%]; P value for interaction, .02). Conclusions and Relevance: Among patients with cerebellar ICH, surgical hematoma evacuation, compared with conservative treatment, was not associated with improved functional outcome. Given the null primary outcome, investigation is necessary to establish whether there are differing associations based on hematoma volume.
CRIS-Team Scopus Importer:2019-10-15

Cell cycle re-entry sensitizes podocytes to injury induced death - Hagen, Manuel; Pfister, Eva; Kosel, Andrea; Shankland, Stuart; Pippin, Jeffrey; Amann, Kerstin Ute; Daniel, Christoph (Cell Cycle, 2016)
Podocytes are terminally differentiated renal cells, lacking the ability to regenerate by proliferation. However, during renal injury, podocytes re-enter into the cell cycle but fail to divide. Earlier studies suggested that re-entry into cell cycle results in loss of podocytes, but a direct evidence for this is lacking. Therefore, we established an in vitro model to test the consequences of re-entry into the cell cycle on podocyte survival. A mouse immortalized podocyte cell line was differentiated to non-permissive podocytes and stimulated with e.g. growth factors. Stimulated cells were analyzed for mRNA-expression or stained for cell cycle analysis using flow cytometry and immunocytofluorescence microscopy. After stimulation to re-entry into cell cycle, podocytes were stressed with puromycin aminonucleoside (PAN) and analyzed for survival. During permissive stage more than 40% of immortalized podocytes were in the S-phase. In contrast, S-phase in non-permissive differentiated podocytes was reduced to 5%. Treatment with b-FGF dose dependently induced re-entry into cell cycle increasing the number of podocytes in the S-phase to 10.7% at an optimal bFGF dosage of 10 ng/ml. Forty eight hours after stimulation with bFGF the number of bi-nucleated podocytes significantly increased. A secondary injury stimulus significantly reduced podocyte survival preferentially in bi-nucleated podocytes In conclusion, stimulation of podocytes using bFGF was able to induce re-entry of podocytes into the cell cycle and to sensitize the cells for cell death by secondary injuries. Therefore, this model is appropriate for testing new podocyte protective substances that can be used for therapy.
EVALuna:32169

Cerebral lipogranuloma: A penetrating traumatic brain injury - Hagen, Manuel; Coras, Roland; Engelhorn, Tobias; Schwab, Stefan; Seifert, Frank (Neurology, 2020)
CRIS-Team Scopus Importer:2020-12-11

Characteristics in Non-Vitamin K Antagonist Oral Anticoagulant-Related Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Sembill, Jochen; Sprügel, Maximilian; Hagen, Manuel; Knappe, Ruben U.; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Stroke, 2019)
Background and Purpose Given inconclusive studies, it is debated whether clinical and imaging characteristics, as well as functional outcome, differ among patients with intracerebral hemorrhage (ICH) related to vitamin K antagonists (VKA) versus non-vitamin K antagonist (NOAC)-related ICH. Notably, clinical characteristics according to different NOAC agents and dosages are not established.
CRIS-Team WoS Importer:2019-06-18

Hematoma enlargement characteristics in deep versus lobar intracerebral hemorrhage - Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Sprügel, Maximilian; Röder, Sebastian; Madžar, Dominik; Hagen, Manuel; Lücking, Hannes; Dörfler, Arnd; Schwab, Stefan; Huttner, Hagen; Hölter, Philip (Annals of Clinical and Translational Neurology, 2020)
Objective: Hematoma enlargement (HE) is associated with clinical outcomes after supratentorial intracerebral hemorrhage (ICH). This study evaluates whether HE characteristics and association with functional outcome differ in deep versus lobar ICH. Methods: Pooled analysis of individual patient data between January 2006 and December 2015 from a German-wide cohort study (RETRACE, I + II) investigating ICH related to oral anticoagulants (OAC) at 22 participating centers, and from one single-center registry (UKER-ICH) investigating non-OAC-ICH patients. Altogether, 1954 supratentorial ICH patients were eligible for outcome analyses, which were separately conducted or controlled for OAC, that is, vitamin-K-antagonists (VKA, n = 1186) and non-vitamin-K-antagonist-oral-anticoagulants (NOAC, n = 107). Confounding was addressed using propensity score matching, cox regression modeling and multivariate modeling. Main outcomes were occurrence, extent, and timing of HE (>33%/>6 mL) and its association with 3-month functional outcome. Results: Occurrence of HE was not different after deep versus lobar ICH in patients with non-OAC-ICH (39/356 [11.0%] vs. 36/305 [11.8%], P = 0.73), VKA-ICH (249/681 [36.6%] vs. 183/505 [36.2%], P = 0.91), and NOAC-ICH (21/69 [30.4%] vs. 12/38 [31.6%], P = 0.90). HE extent did not differ after non-OAC-ICH (deep:+59% [40–122] vs. lobar:+74% [37–124], P = 0.65), but both patients with VKA-ICH and NOAC-ICH showed greater HE extent after deep ICH [VKA-ICH, deep: +94% [54–199] vs. lobar: +56% [35–116], P < 0.001; NOAC-ICH, deep: +74% [56–123] vs. lobar: +40% [21–49], P = 0.001). Deep compared to lobar ICH patients had higher HE hazard during first 13.5 h after onset (Hazard ratio [HR]: 1.85 [1.03–3.31], P = 0.04), followed by lower hazard (13.5–26.5 h, HR: 0.46 [0.23–0.89], P = 0.02), and equal hazard thereafter (HR: 0.96 [0.56–1.65], P = 0.89). Odds ratio for unfavorable outcome was higher after HE in deep (4.31 [2.71–6.86], P < 0.001) versus lobar ICH (2.82 [1.71–4.66], P < 0.001), and only significant after small-medium (1st volume-quarter, deep: 3.09 [1.52–6.29], P < 0.01; lobar: 3.86 [1.35–11.04], P = 0.01) as opposed to large-sized ICH (4th volume-quarter, deep: 1.09 [0.13–9.20], P = 0.94; lobar: 2.24 [0.72–7.04], P = 0.17). Interpretation: HE occurrence does not differ among deep and lobar ICH. However, compared to lobar ICH, HE after deep ICH is of greater extent in OAC-ICH, occurs earlier and may be of greater clinical relevance. Overall, clinical significance is more apparent after small–medium compared to large-sized bleedings.
CRIS-Team Scopus Importer:2020-03-17

Heparin for prophylaxis of venous thromboembolism in intracerebral haemorrhage - Sprügel, Maximilian; Sembill, Jochen; Kuramatsu, Joji; Gerner, Stefan; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2019)
Objective: To determine the occurrence of intracranial haemorrhagic complications (IHC) on heparin prophylaxis (low-dose subcutaneous heparin, LDSH) in primary spontaneous intracerebral haemorrhage (ICH) (not oral anticoagulation-associated ICH, non-OAC-ICH), vitamin K antagonist (VKA)-associated ICH and non-vitamin K antagonist oral anticoagulant (NOAC)-associated ICH. Methods: Retrospective cohort study (RETRACE) of 22 participating centres and prospective single-centre study with 1702 patients with VKA-associated or NOAC-associated ICH and 1022 patients with non-OAC-ICH with heparin prophylaxis between 2006 and 2015. Outcomes were defined as rates of IHC during hospital stay among patients with non-OAC-ICH, VKA-ICH and NOAC-ICH, mortality and functional outcome at 3 months between patients with ICH with and without IHC. Results: IHC occurred in 1.7% (42/2416) of patients with ICH. There were no differences in crude incidence rates among patients with VKA-ICH, NOAC-ICH and non-OAC-ICH (log-rank p=0.645; VKA-ICH: 27/1406 (1.9%), NOAC-ICH 1/130 (0.8%), non-OAC-ICH 14/880 (1.6%); p=0.577). Detailed analysis according to treatment exposure (days with and without LDSH) revealed no differences in incidence rates of IHC per 1000 patient-days (LDSH: 1.43 (1.04-1.93) vs non-LDSH: 1.32 (0.33-3.58), conditional maximum likelihood incidence rate ratio: 1.09 (0.38-4.43); p=0.953). Secondary outcomes showed differences in functional outcome (modified Rankin Scale=4-6: IHC: 29/37 (78.4%) vs non-IHC: 1213/2048 (59.2%); p=0.019) and mortality (IHC: 14/37 (37.8%) vs non-IHC: 485/2048 (23.7%); p=0.045) in disfavour of patients with IHC. Small ICH volume (OR: volume <4.4 mL: 0.18 (0.04-0.78); p=0.022) and low National Institutes of Health Stroke Scale (NIHSS) score on admission (OR: NIHSS <4: 0.29 (0.11-0.78); p=0.014) were significantly associated with fewer IHC. Conclusions: Heparin administration for venous thromboembolism (VTE) prophylaxis in patients with ICH appears to be safe regarding IHC among non-OAC-ICH, VKA-ICH and NOAC-ICH in this observational cohort analysis. Randomised controlled trials are needed to verify the safety and efficacy of heparin compared with other methods for VTE prevention.
CRIS-Team Scopus Importer:2019-05-02
Keywords: cerebrovascular disease; critical care; intracerebral heamorrhage; stroke

Influence of new versus traditional antiepileptic drugs on course and outcome of status epilepticus - Reindl, Caroline; Sprügel, Maximilian; Sembill, Jochen; Müller, Tamara; Hagen, Manuel; Gerner, Stefan; Kuramatsu, Joji; Hamer, Hajo; Huttner, Hagen; Madžar, Dominik (Seizure-European Journal of Epilepsy, 2020)
Purpose: New antiepileptic drugs (AEDs) are increasingly applied in second-line therapy of status epilepticus (SE). In our study, we analyzed the impact of the choice of second-line AEDs on the course and prognosis of SE. Methods: This retrospective single- center study used data of an 8 year cohort of SE in adults from 2007 to 2014. Based on the year of market introduction with a cutoff at 1990, we classified AEDs as traditional or new. Prescription pattern associated differences in prognosis were measured through univariate and multivariable analysis of 3 endpoints: occurrence of refractory SE (RSE), functional outcome in survivors to discharge (good: mRS at discharge <3 or identical to admission mRS; otherwise poor), and in-hospital mortality. Results: From 362 SE episodes during the study period, 222 episodes were included into the study, among those 150 episodes treated with new and 72 with traditional AEDs. Use of new AEDs increased during the study period. After adjustment for confounders, treatment with new AEDs was on the one hand associated with higher rate of RSE occurrence (OR 1.95, 95 % CI 1.05–3.62, p = 0.03), but, on the other hand, also with better functional outcome at discharge (OR 2.64, 95 % CI 1.16–6.00, p = 0.02), while it was not an independent predictor of in- hospital mortality (OR 0.88, 95 % CI 0.33–2.33, p = 0.80). Conclusion: Our observation that new AEDs may be associated with a higher rate of RSE development and relatively better functional outcome when adjusted for the premorbid mRS needs confirmation in prospective studies.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Anticonvulsant; Antiepileptic drug; Established status epilepticus; Functional outcome; Mortality; Refractoriness; Status epilepticus; Treatment

Management of therapeutic anticoagulation in patients with intracerebral haemorrhage and mechanical heart valves - Kuramatsu, Joji; Sembill, Jochen; Gerner, Stefan; Sprügel, Maximilian; Hagen, Manuel; Röder, Sebastian; Endres, Matthias; Haeusler, Karl Georg; Sobesky, Jan; Schurig, Johannes; Zweynert, Sarah; Bauer, Miriam; et al. (European Heart Journal, 2018)
Aims Evidence is lacking regarding acute anticoagulation management in patients after intracerebral haemorrhage (ICH) with implanted mechanical heart valves (MHVs). Our objective was to investigate anticoagulation reversal and resumption strategies by evaluating incidences of haemorrhagic and thromboembolic complications, thereby defining an optimal time-window when to restart therapeutic anticoagulation (TA) in patients with MHV and ICH. Methods and results We pooled individual patient- data (n = 2504) from a nationwide multicentre cohort-study (RETRACE, conducted at 22 German centres) and eventually identified MHV-patients (n = 137) with anticoagulation-associated ICH for outcome analyses. The primary outcome consisted of major haemorrhagic complications analysed during hospital stay according to treatment exposure (restarted TA vs. no-TA). Secondary outcomes comprised thromboembolic complications, the composite outcome (haemorrhagic and thromboembolic complications), timing of TA, and mortality. Adjusted analyses involved propensity-score matching and multivariable cox-regressions to identify optimal timing of TA. In 66/137 (48%) of patients TA was restarted, being associated with increased haemorrhagic (TA = 17/66 (26%) vs. no-TA = 4/71 (6%); P < 0.01) and a trend to decreased thromboembolic complications (TA = 1/66 (2%) vs. no-TA = 7/71 (10%); P = 0.06). Controlling treatment crossovers provided an incidence rate-ratio [hazard ratio (HR) 10.31, 95% confidence interval (CI) 3.67-35.70; P < 0.01] in disadvantage of TA for haemorrhagic complications. Analyses of TA-timing displayed significant harm until Day 13 after ICH (HR 7.06, 95% CI 2.33-21.37; P < 0.01). The hazard for the composite-balancing both complications, was increased for restarted TA until Day 6 (HR 2.51, 95% CI 1.10-5.70; P = 0.03). Conclusion Restarting TA within less than 2 weeks after ICH in patients with MHV was associated with increased haemorrhagic complications. Optimal weighing-between least risks for thromboembolic and haemorrhagic complications-provided an earliest starting point of TA at Day 6, reserved only for patients at high thromboembolic risk.
EVALuna2:34917

Monitoring in the follow up of patients after EVT. Could pupillometry replace repetitive CT-control? - Köhn, Julia; Borutta, Matthias; Giede-Jeppe, Antje; Hagen, Manuel; Kuramatsu, Joji; Schwab, Stefan; Huttner, Hagen (Journal für Anasthesie und Intensivbehandlung, 2021)
CRIS-Team Scopus Importer:2024-12-16

Simplified Edinburgh CT Criteria for Identification of Lobar Intracerebral Hemorrhage Associated With Cerebral Amyloid Angiopathy - Sembill, Jochen; Knott, Michael; Xu, Mingming; Röder, Sebastian; Hagen, Manuel; Sprügel, Maximilian; Mrochen, Anne; Borutta, Matthias; Hölter, Philip; Engelhorn, Tobias Martin; Rothhammer, Veit; Macha, Kosmas; et al. (Neurology, 2022)
BACKGROUND AND OBJECTIVES: In patients with lobar intracerebral hemorrhage (ICH), etiologic characterization represents a tradeoff between feasibility, resource allocation, and diagnostic certainty. This study investigated the accuracy and clinical utility of the simplified Edinburgh CT criteria to identify underlying cerebral amyloid angiopathy (CAA). METHODS: This external validation analyzed 210 consecutive patients with lobar ICH and available CT and MRI studies from a prospective single-center observational cohort study (2006-2015, Longitudinal Cohort Study on ICH Care [UKER-ICH,] NCT03183167). We investigated the interrater variability and diagnostic accuracy of the simplified Edinburgh CT-based criteria for identification of ICH associated with probable CAA according to MRI-based modified Boston criteria as a reference standard. We evaluated the utility of the simplified Edinburgh criteria by decision curve analysis, comparing the theoretical clinical net benefit (weighted benefit-harm at varying threshold probabilities) of the high-risk category (finger-like projections and subarachnoid hemorrhage) for ruling in and the low-risk category (neither finger-like projections nor subarachnoid hemorrhage) for ruling out with the assumptions of no or all patients having CAA (default strategies). RESULTS: Of 210 patients, 70 (33.3%) had high risk, 67 (31.9%) had medium risk, and 73 (34.8%) had low risk for CAA-associated ICH according to simplified Edinburgh CT criteria, showing moderate interrater variability. Discrimination was good (area under the receiver operating characteristics curve 0.74, 95% CI 0.67-0.81) without evidence of poor calibration (Hosmer-Lemeshow, p = 0.54) for validation of MRI-based diagnosis of probable CAA (n = 94 of 210, 44.8%). The rule-in criteria (high risk), had 87.1% (79.3%-92.3%) specificity, and the rule-out criteria (low risk), had 80.9% (71.1%-88.0%) sensitivity. Decision curve analysis suggested a theoretical clinical net benefit for ruling in but not for ruling out probable CAA compared to default strategies. DISCUSSION: Applying the simplified Edinburgh CT criteria during diagnostic workup seems clinically useful and may accurately identify CAA in patients with lobar ICH. TRIAL REGISTRATION INFORMATION: ClinicalTrials.gov Identifier: NCT03183167. CLASSIFICATION OF EVIDENCE: This study provides Class II evidence that in patients with lobar hemorrhages, the simplified Edinburgh criteria accurately identify those at high risk of CAA.
CRIS-Team Scopus Importer:2022-06-03

Systemic inflammatory response syndrome and long-term outcome after intracerebral hemorrhage - Hagen, Manuel; Sembill, Jochen; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Lücking, Hannes; Hölter, Philip; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, Neuroimmunology and Neuroinflammation, 2019)
ObjectiveTo investigate whether the systemic inflammatory response syndrome (SIRS) without infection as surrogate of a systemic immune response is associated with poor long-term functional outcome in patients with spontaneous intracerebral hemorrhage (ICH).MethodsWe analyzed consecutive patients with spontaneous ICH from our prospective cohort study (2018-2015). SIRS was defined according to standard criteria: i.e., 2 or more of the following parameters during hospitalization: body temperature <36°C or >38°C, respiratory rate >20 per minute, heart rate >90 per minute, or white blood cell count <4,000/L or >12,000/L in the absence of infection. The primary outcome consisted of the modified Rankin Scale (mRS) at 3 and 12 months investigated by adjusted ordinal shift analyses. Bias and confounding were addressed by propensity score matching and multivariable regression models.ResultsOf 780 patients with ICH, 21.8% (n = 170) developed SIRS during hospitalization. Patients with SIRS showed more severe ICH compared with those without; i.e., larger ICH volumes (18.3 cm3, interquartile range [IQR 4.6-47.2 cm3] vs 7.4 cm3, IQR [2.4-18.6 cm3]; p < 0.01), increased intraventricular hemorrhage (57.6%, n = 98/170 vs 24.8%, n = 79/319; p < 0.01), and poorer neurologic admission status (NIH Stroke Scale score 16, IQR [7-30] vs 6, IQR [3-12]; p < 0.01). ICH severity-adjusted analyses revealed an independent association of SIRS with poorer functional outcome after 3 (OR 1.80, 95% CI [1.08-3.00]; p = 0.025) and 12 months (OR 1.76, 95% CI [1.04-2.96]; p = 0.034). Increased ICH volumes on follow-up imaging (OR 1.38, 95% CI [1.01-1.89]; p = 0.05) and previous liver dysfunction (OR 3.01, 95% CI [1.03-10.19]; p = 0.04) were associated with SIRS.ConclusionsIn patients with ICH, we identified SIRS to be predictive of poorer long-term functional outcome over the entire range of mRS estimates. Clinically relevant associations with SIRS were documented for previous liver dysfunction and hematoma enlargement.
CRIS-Team Scopus Importer:2019-10-29